Temporal Response of Endogenous Neural Progenitor Cells Following Injury to the Adult Rat Spinal Cord - Mao, Yilin; Mathews, Kathryn; Gorrie, Catherine A. (Frontiers in Cellular Neuroscience, 2016)
A pool of endogenous neural progenitor cells found in the ependymal layer and the sub-ependymal area of the spinal cord are reported to upregulate nestin in response to traumatic spinal cord injury. These cells could potentially be manipulated within a critical time period offering one innovative approach to the repair of spinal cord injury. However, little is known about the temporal response of endogenous neural progenitor cells following spinal cord injury. This study used a mild contusion injury in rat spinal cord and immunohistochemistry to determine the temporal response of ependymal neural progenitor cells following injury and their correlation to astrocyte activation at the lesion site. The results from the study demonstrated that Nestin staining intensity at the central canal peaked at 24 hours post-injury and then gradually declined over time. Reactive astrocytes double labelled by Nestin and GFAP were found at the lesion edge and commenced to form the glial scar from 1 week after injury. We conclude that the critical time period for manipulating endogenous neural progenitor cells following a spinal cord injury in rats is between 24 hrs when nestin expression in ependymal cells is increased and 1 week when astrocytes are activated in large numbers.